Behind the trend of Englishing the business names in Aceh, Indonesia: A postcolonial analysis - Usman, Jarjani; Faridah, Nurul; Mulia, Mulia (Universitas Islam Negeri Banda Aceh, 2021)
This study critically analyzes the recent trend of Englishing shop names in Aceh province. Borrowing Bhabha’s postcolonial theory, this study attempted to uncover the shop owners’ perceptions of privileging English and marginalizing local languages, even though their customers are mostly local. Data collection was by taking pictures and interviewing 20 owners of the shops, four females and 16 males. Results show that the 120 shop names in Banda Aceh and surrounding it are in English, modified English and Indonesian ordering, hybridized English and Indonesian ordering, hybridized English Acehnese language and English, English and English ordering, and mixed owner’s names and English ordering. They voluntarily mimicked the Western culture by using English names because they believe that English is marketable, modern, practical, flexible, familiar, and short for shop branding, while the local language looks not modern, unpractical, and weird. In conclusion, most shop owners in the two districts in Aceh negotiate the Western hegemony for the economic benefits.